Application abdominal massage in reducing constipation in patients with traction - Rahmasari, Ikrima; Sofiani, Yani; Yunitri, Ninik; Budiati, Dhiani (Riset Informasi Kesehatan, 2024)
Backgrounds: Fractures represent a potential or actual threat to a person's integrity. Fracture management includes conservative measures and surgery. One of the conservative measures is the installation of protective traction. The purpose of traction training is to reduce spasm, reposition and immobilization. Immobilization is a limitation of independence, physical movement of the body or one or more extremities which is often caused by movement restrictions in the form of bed rest, physical restrictions due to external equipment (for example casts or skeletal traction), restrictions on voluntary movements, or physical disorders. There are various physical problems that can occur in a state of immobility, one of which is the problem of changes in fecal elimination, namely constipation. Abdominal massage is a complementary therapy that can be used as an effective intervention to treat constipation without causing side effects. Method: application of Evidence Based Practice (EBNP) with evidence sourcesobtained from the Pubmed journal. The article was published in 2020. Searches were carried out in several databases, namely the Cochrane Library, Biomed Central, MEDLINE (EBSCOhost), MEDLINE (PubMed), and Scopus. The author carried out screening using the PICO formulation. Results: Data analysis results were processed using Jamovi with the one sample T-Test statistical test. The average reduction in constipation was found before and after abdominal massage with a P-Value of 0.001. Conclusion: There is a significant difference in reducing constipation before and after giving abdominal massage with P-Value <0.005.).